Penggunaan Tanaman Herbal Untuk Kesehatan - Susilo Yulianto (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract: The use of herbs, for health. Herbs are plants that can be used as drugs both leaves, stems, or roots. Herbs is partly used by the community for traditional or alternative medicine. Besides, the herb also has the advantage, that does not have side effects, treatment can be carried out by family members sendiri.Tanaman is an alternative herbal treatment that has been done by the people of Indonesia have traditionally. The successful use of herbal plants is strongly influenced by people's knowledge about the benefits of each type of medicinal plants, especially herbs that have been studied empirically. It is also influenced by how the use of each herb for a variety of different diseases. This study aims to determine the use of herbs for health. This research method is descriptive, with a sample of 53 respondents drawn by simple random sampling technique. The data collection conducted direct interviews with respondents and the open-air observation. Research instrument used was a questionnaire. The result showed that all respondents had been using herbs for health. The conclusion of this study was the use of herbs for health still needs to be improved further by providing the knowledge, awareness, willingness and ability of thecommunity.